Tobacco smoking effect on HIV-1 pathogenesis: role of cytochrome P450 isozymes. (November 2013) - Ande, Anusha; McArthur, Carole; Kumar, Anil; Kumar, Santosh
<x xml:space="preserve">Abstract</x> Introduction: Tobacco smoking is highly prevalent among the HIV-1-infected population. In addition to diminished immune response, smoking has been shown to increase HIV-1 replication and decrease response to antiretroviral therapy, perhaps through drug–drug interaction. However, the mechanism by which tobacco/nicotine increases HIV-1 replication and mediates drug–drug interaction is poorly understood. Areas covered: In this review, the authors discuss the effects of smoking on HIV-1 pathogenesis. Since they propose a role for the cytochrome P450 (CYP) pathway in smoking-mediated HIV-1 pathogenesis, the authors briefly converse the role of CYP enzymes in tobacco-mediated oxidative stress and toxicity. Finally, the authors focus on the role of CYP enzymes, especially CYP2A6, in tobacco/nicotine metabolism and oxidative stress in HIV-1 model systems monocytes/macrophages, lymphocytes, astrocytes and neurons, which may be responsible for HIV-1 pathogenesis. Expert opinion: Recent findings suggest that CYP-mediated oxidative stress is a novel pathway that may be involved in smoking-mediated HIV-1 pathogenesis, including HIV-1 replication and drug–drug interaction. Thus, CYP and CYP-associated oxidative stress pathways may be potential targets to develop novel pharmaceuticals for HIV-1-infected smokers. Since HIV-1/TB co-infections are common, future study involving interactions between antiretroviral and antituberculosis drugs that involve CYP pathways would also help treat HIV-1/TB co-infected smokers effectively.